Предмет: Алгебра,
автор: balabanova20019
помогите решить уравнение
(х + 3 )(5х -1)-(4х -3)(х + 1)=25+13х
Ответы
Автор ответа:
1
(x+3)(5x-1)-(4x-3)(x+1)=25+13x
5x^2-x+15x-3-4x^2-4x+3x+3=25+13x
x^2-25=0
x^2=25
x=5
5x^2-x+15x-3-4x^2-4x+3x+3=25+13x
x^2-25=0
x^2=25
x=5
balabanova20019:
Спасибо
Похожие вопросы
Предмет: Русский язык,
автор: upuska
Предмет: Другие предметы,
автор: sacfda123
Предмет: Другие предметы,
автор: sacfda123
Предмет: Алгебра,
автор: ksenia202314
Предмет: Қазақ тiлi,
автор: srvsf